Test anxiety among Ilam UMS’ Students, 2012 - Darabi, Maryam; Ashraf Aivazi, Ali; Gholami-Parizad, Eskandar; Ghazanfari, Zeinab; Imanzad, Masoumeh (Advances in Nursing & Midwifery, 2014)
Abstract Background and aim: In today’s era of academic competition test anxiety among students is increasing. Anxiety may result in difficulty in concentration and information processing and hampers students’ performance. The current study aimed to determine test anxiety among Ilam UMS’ students. Method and materials: A descriptive correlational design was used. The sample of the study consisted of one hundred and seventy undergraduate students which were included in the study by stratified random sampling. Data were collected by using Sarason’s Test Anxiety Scale (TAS). Data were collected three weeks prior to examination date and were analyzed using descriptive methods by SPSS software. Findings: Our findings showed that 34.1%, 51.8%, and 14.1% of students experienced mild, moderate, and severe test anxiety levels, respectively. Further, a significant relationship was found between test anxiety score with only residency status at 0.05 level. In other words, nursing, local, and married students showed more test anxiety. However, no relationship was seen between test anxiety with age and gender. Conclusion: since anxiety has negative effects on educational performance, implementing anxiety preventive programs including psychological consulting services, identifying & improving potential causes are suggested. Much more attention should be paid to high risk students, local, and especially married and nursing students. Key words: Test Anxiety Prevalence, Students, Ilam REFERENCES Abulghasemi, A (2008), [Test anxiety, causes, assessment & treatment. Psychological Research],5(3-4),82-97. (Persian) Aghaie, E, Abedi, A & Jamali Paghale, S (2012), [Meta-analysis of the effectiveness of cognitive-behavior interventions in the reduction of test anxiety in Iran. Iranian Journal of Psychiatry & Clinical Psychology] 18(1), 3-12. (Persian) Biabangard, E (2008), Methods of preventing academic failure, Tehran, Parents and Teachers Association . (Persian) Boor, M (1980), Test anxiety and classroom examination performance: a reply to Daniels and Hewitt (1978). Journal of Clinical Psychology , 36(1), 177-9. Cheraghian, B, Fereiduni Moghadam, M, Barazpardanjani, Sh, Bavarsad, N (2008), A review of test anxiety and its relationship with academic performance in nursing students. Knowledge& Health Magazine . 3(3-4), 25-9. (Persian) Clark, JW, Fox, PA & Schneider, HG (1998), Feedback, test anxiety and performance in a college course. Psychological Reports , 82(1),203-8. Eizadifard, R, Sepasi Ashtiani, M (2010), Effectiveness of cognitive-behavioral therapy with problem solving skills training on reduction of test anxiety symptoms. Journal of Behavioral Sciences ,4(1),23-7. (Persian) Hancock, DR (2001), Effects of test anxiety and evaluative threat on students’ achievement and motivation, Journal of Educational Research , 94(5), 284-90. 1392 زییاپ ،82 هرامش ،23 هرود / 6 ناراکمه و یباراد میرم Hatami, Z & Ardalan, M (2010), Assessment of the level of test anxiety in the students of the Kurdistan University of Medical Sciences & its related factors. Scientific Journal of Kurdistan University of Medical Sciences ,14(4),99-105. (Persian) Heravi, M, Jadid Milani, M, Regea, N, Valaie, N(2004), The effect of relaxation training on exam driven anxiety level among nursing students. Journal Mazandaran Univ Med Sci ,14(43),86-92. (Persian) Jomee Pour, A, (2006), Freedom from anxiety, Mashhad, Faragozinesh . (Persian) Khadivzadeh, T, Seif, AA & Valaei, N (2002), Learning and study strategy and success rate in university students, Mashhad University of Medical Sciences, 1999. Pejouhandeh ,7(1),35-42. (Persian) Khosravi, M & Bigdely, IA, (2008), The relationship between personality factors and test anxiety among university students. Journal of Behavioral Sciences ,2(1),13-24. (Persian) Lashkaripour, K, Bakhshani, NM & Solaimani, MJ, (2006), The relationship between test anxiety and academic achievement in students of guidance schools in Zahedan in 2006. Zahedan Journal of Research in Medical Sciences (Tabib-E-Shargh),8(4),253-9. (Persian) Moaadeli, Z, Ghazanfari Hesamabadi, M, 2004, ‘Evaluation of test anxiety in students of nursing and midwifery school of Hazrat Fatima (SA) Spring 2004’. Strides in development of medical education ,1(2),65-72. (Persian) Mousavi, M, Haghshenas, H, Alishahi, M, Najmi, B,l (2008), Anxiety test and some correlated socio-demographic factors in high school students in Shiraz. Journal of Research in Behavioral Sciences , 6(1),17-25. (Persian)